2009
DOI: 10.1177/0884533609335376
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Supplementation Lowers C‐Reactive Protein Levels Independent of Triglyceride Reduction in Patients With End‐Stage Renal Disease

Abstract: The study demonstrates that consuming 960 mg/d of EPA and 600 mg/d of DHA can lower CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
3
47
1
1
Order By: Relevance
“…22 In addition, fish-oil supplementation lowered CRP levels in patients with end-stage renal disease. 23 Although our findings do not firmly establish a causative association, the temporal sequence of these effects suggests that ω-3 PUFAs may have attenuated the inflammatory response in a manner that minimizes tissue injury while avoiding suppression of those components of inflammation necessary for subsequent wound healing. Dampening the magnitude of the inflammatory response might facilitate resolution of inflammation and transition to wound healing.…”
Section: Outcome Datacontrasting
confidence: 69%
“…22 In addition, fish-oil supplementation lowered CRP levels in patients with end-stage renal disease. 23 Although our findings do not firmly establish a causative association, the temporal sequence of these effects suggests that ω-3 PUFAs may have attenuated the inflammatory response in a manner that minimizes tissue injury while avoiding suppression of those components of inflammation necessary for subsequent wound healing. Dampening the magnitude of the inflammatory response might facilitate resolution of inflammation and transition to wound healing.…”
Section: Outcome Datacontrasting
confidence: 69%
“…Another hypothesis for the cardioprotective effects of fish oil supplementation is the inhibition of cytokine production, as measured directly in plasma or ex vivo, and studies have been published that support and challenge the hypothesis that n-3 LCP inhibit cytokine and CRP production (102,103,(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150) . In their recent meta-analysis including twenty-one trials, Balk et al (151) concluded that the effect of n-3 LCP, including EPA and DHA, on CRP levels in human subjects was unconvincing.…”
Section: Effects Of Epa and Dha On Inflammationmentioning
confidence: 99%
“…32 ω3-PUFA-rich fish oil reduced CRP concentrations in patients with end-stage renal disease. 59 Our results indicate that ω3-PUFA treatment reduces the inflammatory response in DF patients, and this observation suggests that complementary treatment with ω3-PUFA could be used Fig. 2 Treatment with ω3-PUFA decreases serum IL-6 and Creactive protein (CRP) concentrations in patients with digestive fistulas (DF).…”
Section: Discussionmentioning
confidence: 92%